Consumption of fruits, vegetables, and legumes are associated with overweight/obesity in the middle- and old-aged Chongqing residents: A case-control study. Issue 27 (8th July 2022) - Wu, E; Ni, Juntao; Zhou, Wei; You, Leiying; Tao, Lin; Xie, Tian
Abstract : This study aimed to investigate the association of dietary habits with the risk of overweight/obesity among middle-and-old-aged Chongqing residents and also to examine the joint effects of behavioral lifestyles, dietary habits, and overweight/obesity. In this case-control study, age (±3 years), sex, and time of physical exercise matched 979 overweight/obesity residents, and 979 normal weight residents were recruited. A validated questionnaire was used to collect participants' information. Conditional logistic regression analysis was performed to determine the adjusted odds ratios (ORs) and 95% CIs of dietary habits and lifestyles associated with overweight/obesity risk. Overweight/obesity was defined as body mass index (BMI) ≥ 24 kg·m −2, and normal weight was defined as 18.5 ≤ BMI < 24 kg·m −2 . The multivariate-adjusted models showed the weekly intake frequency of fruits 0–1 (day/week) (OR = 1.79, 95% CI = 1.04–3.10), and legumes 0–1 (day/week) (OR = 2.45, 95% CI = 1.28–4.67), as well as the weekly intake percentage of vegetables ≥ 15% (OR = 2.44, 95% CI = 1.04–5.71) were associated with a higher risk of overweight/obesity. Besides, there were joint effects of lifestyles (smoking or drinking) and dietary habits on overweight/obesity risk ( P for interaction < 0.05). The consumption of vegetables, fruits, legumes, and the joint effects of behavioral habits (smoking or drinking) may modify the risk of being overweight/obese. It is essential to consume fruits and legumes at least 2 days/week, quit smoking, and stop consuming alcohol to avoid overweight/obesity among middle-aged and elderly people in Chongqing, China.